Effect of particle size and bed height on the characteristic of a fluidized bed dryer. Issue 1 (1st January 2020) - Yohana, Eflita; Muchammad,; Tauviqirrahman, Mohammad; Sayekti, Awallina Ani; Choi, Kwang-Hwan; Paramita, Vita
Abstract: Food, pharmaceutical, mineral and petroleum industries often use fluidized bed dryers for the drying process. In the present study, fluidized bed dryers in the tea processing industry is of particular interest. The main aim of this work is to investigate the effect of on the static bed height on the the coefficient of heat transfer in the fluidized bed dryer. In addition, the effect of particle size variations on the bed pressure drop in a fluidized bed dryer is also explored based on the computational fluid dynamics (CFD) approach. The multiphase, solid, and gas Eulerian-Eulerian models are employed to investigate the behavior of the fluidized bed dryers. The solid gas interphase interactions is predicted by the Syamlal O'Brien and Gidaspow drag models. To get more accurate results, a 3D fluidized bed model is applied. The analysis is performed by varying the particle sizes and the static bed heights. The simulation results show that the pressure drop increases with the increase in the particle size in the fluidized bed dryer. In addition, the effect of bed height variations on the coefficient of the heat transfer is also quite significant. The difference in the coefficient of the heat transfer values for each height of the static bed is highlighted. It is also found that when the height of the bed is higher, the efficiency of air to particle heat transfer becomes lower.